Surfactant-enhanced remediation of oil-contaminated soil and groundwater: A review - Liu, Jian-Wu; Wei, Kun-Hao; Xu, Shao-Wei; Cui, Jun; Ma, Jie; Xiao, Xiao-Long; Xi, Bei-Dou; He, Xiao-Song (The Science of the total environment, 2021)
Oil leakage, which is inevitable in the process of extraction, processing, transportation and storage, seriously undermines the soil and groundwater environment. Surfactants can facilitate the migration and solution of oil contaminants from nonaqueous phase liquid (NAPL) or solid phase to water by reducing the (air/water) surface tension, (oil/water) interfacial tension and micellar solubilization. They can effectively enhance the hydrodynamic driven remediation technologies by improving the contact efficiency of contaminants and liquid remediation agents or microorganism, and have been widely used to enhance the remediation of oil-contaminated sites. This paper summarizes the characteristics of different types of surfactants such as nonionic, anionic, biological and mixed surfactants, their enhancements to the remediation of oil-contaminated soil and groundwater, and examines the factors influencing surfactant performance. The causes of tailing and rebound effects and the role of surfactants in suppressing them are also discussed. Laboratory researches and actual site remediation practices have shown that various types of surfactants offer diverse options. Biosurfactants and mixed surfactants are superior and worth attention among the surfactants. Using surfactant foams, adding shear-thinning polymers, and combining surfactants with in-situ chemical oxidation are effective ways to resolve tailing and rebound effects. The adsorption of surfactants on soils and aquifer sediments decreases remediation efficiency and may cause secondary pollution, Therefore the adsorption loss should be noticed and minimized. [Display omitted] •Surfactant enhanced remediation through mobilization and solubilization effects.•Biosurfactants and mixed surfactants show great application potential.•Co-injection of foams or xanthan improves uniform distribution of surfactants.•Surfactant-enhanced in-situ chemical oxidation eliminates tailing and rebound.